Gender and Racial Identity, Smoking Norms, and Smoking Behaviors Among College-Aged African American Women - Thornton, Shelly A. (East Carolina University, 2018)
African American women smoke less than their gender and racial counterparts, yet they face higher risk for smoking-related disease development, disease mortality, and poorer disease related quality of life. Therefore, it is important to identify factors that may contribute to or protect against smoking initiation within this population. Social Identity Theory (SIT) may offer a framework for understanding gender and racial influences on smoking. SIT posits that individuals strengthen their sense of belonging with social groups by adopting sets of normative perceptions, attitudes, values, and behaviors. Prior research has established associations between gender and racial identity, normative perceptions of smoking, and smoking behavior, therefore smoking may be a behavior that reinforces gender and racial identity. Female gender seems to be protective across the developmental continuum, however African American cultural influences on smoking seem to function differently. In adolescence, racial identity seems to protect against smoking, but mixed findings from research studies with adults show variable results with racial identity appearing to be a risk factor for smoking in some results and a protective factor in other results, and this may be related to changing normative perceptions of smoking for African Americans from adolescence to adulthood. To date, the research examining the aforementioned links between gender and racial identity, perceived smoking norms, and smoking behavior can be characterized as preliminary. Existing research also lacks a potential unifying theory and measurement, particularly of gender and racial identity, and has been limited in terms of comprehensiveness and comparability across gender and racial domains. This thesis sought to examine gender and racial influences on smoking behavior in a sample of African American college-aged women guided by the SIT theoretical framework. More specifically, this study sought to (1) comprehensively measure gender and racial identity domains and compare strengths of identity across these two domains, (2) examine perceived gender and racial smoking norms, (3) determine whether gender and racial identity predict smoking behavior, (4) determine whether gender and race-related smoking norms predict smoking behavior, and (5) examine links between gender identity and gender-related smoking norms and links between racial identity and race-related smoking norms. A total of 168 African American undergraduate women completed an online survey that assessed multiple dimensions of gender and racial identity, normative perceptions of smoking for gender and race, and smoking behavior. On average, participants reported strong, positive feelings towards being women and African American. They also reported that smoking is less typical among the narrower reference group of their female, African American friends, but more typical among the broader reference groups of women in general and African Americans in general. Overall, smoking was perceived to be more normative for African Americans than for women. While the full model of SIT was not supported in terms of the influence of gender or racial identity on norms and smoking, results suggest that having strong positive feelings associated with one's identity as a woman may have a marginal influence on smoking behavior. Overall, smoking behavior among African American women was not strongly influenced by gender or racial identity and may be best understood in relation to gender- and race-related smoking norms. Clinical implications of these findings and future directions for research are discussed.
Keywords: Smoking Norms; Health Disparities; African American women college students--Tobacco use--Psychological aspects; African American women--Race identity; African American women--Health and hygiene; Gender identity